Stationary equilibria in discounted stochastic games with weakly interacting players - Ulrich Horst (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2002)
We give sufficient conditions for a non-zero sum discounted stochastic game with compact and convex action spaces and with norm-continuous transition probabilities, but with possibly unbounded state space to have a N ash equilibrium in homogeneous Markov strategies that depends in a Lipsehitz continuous manner on the current state. H the underlying state space is compact this yields the existence of a stationary equilibrium. For a special class of stochastic games which arise in microstructure models for financial markets we establish the existence of equilibria which guarantee that the state sequence converges in distribution to a unique stationary measure.
urn:nbn:de:kobv:11-10049475
Keywords: D81; E32; 330; Stochastic Games; Stationary Equilibria; Microstructure Models for Financial Markets